Livelihoods at the Margins: Smallholder Vulnerability, Structural Constraints, and Rural Development Pathways in Georgia’s Pastoral Sheep Sector - Mikeladze, Aleksandre (European Journal of Social Science Education and Research, 2026)
In many post-Soviet transition economies, smallholder pastoral systems persist as a primary livelihood base for rural households while simultaneously remaining structurally marginalised from formal markets and policy frameworks. Georgia’s sheep sector exemplifies this tension: concentrated in ecologically distinctive regions such as the Kakheti Steppes and the highland-lowland transhumance corridor of Tusheti, it sustains smallholder families whose economic position is shaped less by resource scarcity than by fragmented organisational structures, land tenure insecurity, degraded communal pastures, and unequal chain governance. Drawing on a primary socio-economic survey of 71 shepherd households (SABUKO, 2024a), national production and trade statistics, and a systematic value chain analysis, this paper examines the structural conditions that suppress income stability and market participation among smallholder producers. It situates these findings within the Sustainable Livelihoods Framework and the broader literature on agricultural transition in post-Soviet economies. The analysis identifies pasture degradation, limited knowledge of sustainable grazing practices, aggregation failures, and institutional certification gaps as compounding constraints that concentrate value upstream of smallholder producers. The paper proposes a strategic framework for addressing these constraints, with implications for rural development policy, conservation-linked livelihoods, and the governance of pastoral commons in comparable transition-economy contexts.
Keywords: smallholder livelihoods; pastoral systems; rural vulnerability; post-Soviet transition; sustainable livelihoods framework; Georgia; value chain governance; land tenure; pasture degradation; geographic indication.